2020
DOI: 10.1186/s12933-019-0981-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin, clopidogrel and prasugrel monotherapy in patients with type 2 diabetes mellitus: a double-blind randomised controlled trial of the effects on thrombotic markers and microRNA levels

Abstract: Background: Despite increased atherothrombotic risk in type 2 diabetes mellitus, (T2DM) the best preventative antithrombotic strategy remains undetermined. We defined the effects of three antiplatelet agents on functional readout and biomarker kinetics in platelet activation and coagulation in patients with T2DM. Materials and methods: 56 patients with T2DM were randomised to antiplatelet monotherapy with aspirin 75 mg once daily (OD), clopidogrel 75 mg OD or prasugrel 10 mg OD during three periods of a crosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 55 publications
5
33
0
Order By: Relevance
“…The three miRNAs responsive to P2Y12 inhibition (miR-197, miR-223 and miR-223*) have previously been described as being enriched in platelets [23]. Also, a crossover study including 56 patients with type 2 diabetes mellitus found plasma levels of miR-197 and miR-223 alongside miR-191 and miR-24 to be lower in diabetic patients on the P2Y12 inhibitor prasugrel, compared with aspirin [26]. We have previously reported a decrease of these platelet-related miRNAs in plasma of healthy volunteers upon treatment with P2Y12 inhibitors [23].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The three miRNAs responsive to P2Y12 inhibition (miR-197, miR-223 and miR-223*) have previously been described as being enriched in platelets [23]. Also, a crossover study including 56 patients with type 2 diabetes mellitus found plasma levels of miR-197 and miR-223 alongside miR-191 and miR-24 to be lower in diabetic patients on the P2Y12 inhibitor prasugrel, compared with aspirin [26]. We have previously reported a decrease of these platelet-related miRNAs in plasma of healthy volunteers upon treatment with P2Y12 inhibitors [23].…”
Section: Discussionmentioning
confidence: 92%
“…When miRNA levels were compared before and 6 hours after endotoxin administration, leukocyte-enriched miR-150 was found to have the strongest decrease ( Figure 2, Table S2) [24]. In contrast, miRNAs previously implicated as markers of platelet activation (miR-197, miR-223, miR-26b, miR-191, miR-24; [23,25,26]) showed higher levels after endotoxin treatment. Leukocyte-enriched miR-150 showed strongest fall in abundance, while platelet-enriched miR-197 and miR-223 showed the strongest rise.…”
Section: Effect Of Endotoxemia On Circulating Mirnasmentioning
confidence: 94%
“…We also observed no influence on circulating levels of PMP by antiplatelet therapy in agreement with others [ 37 , 38 ], who showed that aspirin treatment did not change the level of PMP in T2DM. None of the study subjects assumed prasugrel, which shows the most potent effect on platelet inhibition in T2DM [ 39 ]. On the other hand, TF-MPs appeared to be significantly lower in antiplatelet treated patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin regulated miR-155/eNOS (endothelial nitric oxide synthase) pathway and suppressed endothelial cell dysfunction under the inflammation [ 104 ]. Also, aspirin suppressed the expression of miR-24, − 191 and − 197 in plasma [ 105 ].…”
Section: Main Bodymentioning
confidence: 99%